Kontribusi Komunikasi Interpersonal Terhadap Kepuasan Pernikahanan Pada Suami yang Menjalani Pernikahan Jarak Jauh - trikanti, Trikanti; Hadis, Fawzia Aswin; Rahardjo, Wahyu (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study aims to examine the contribution of interpersonal communication to marital satisfaction among husbands engaged in long-distance marriages. Using a quantitative approach, data were analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS version 4.1. The findings indicate that interpersonal communication has a positive and significant influence on marital satisfaction. This is reflected in the path coefficient of 0.652 and a sample mean of 0.660. The f-square value for the interpersonal communication variable was 0.741, indicating a large effect size. With a standard deviation of 0.043, the resulting t-statistic reached 15.286—far exceeding the critical threshold of 1.96—and a p-value of 0.000, confirming the statistical significance of the relationship. These results underscore the crucial role of quality interpersonal communication in maintaining marital satisfaction, even in the context of physical separation. The study implies that enhancing interpersonal communication skills can serve as an effective strategy for couples in long-distance marriages to preserve relationship satisfaction and emotional closeness.